The Role of Green Intellectual Capital and Organizational Reputation in Influencing Environmental Performance - Yadiati, Winwin; Nissa, Nissa; Paulus, Sugiono; Suharman, Harry; Meiryani, Meiryani (International Journal of Energy Economics and Policy, 2019)
The current study fills the gap of the literature by analyzing the contribution of intangible resources in affecting firm's environmental performance. In doing so, the authors aim to examine the contribution of organization's reputation in driving firm's environmental performance. Furthermore, the contribution of the current study is extended to study the crucial role of green intellectual capital in influencing sustainable performance. In this regard, the study measures intellectual capital in the form of green human capital, green social capital and green relational capital in realizing their impact on firm's environmental performance. Confronting the patterns of strict natural traditions and prominent ecological awareness, organizations ought not freeze or overcompensate from the existing ecological regulations as these natural patterns could be moved toward the green practice that may drive them to convey sustainable development and bring consensus in the environmental and organizational objectives. Unlike viewing ecological policies as hindrances of firm's future improvement, the findings of the current study concentrate on finding the right assessment of intangible resources in carrying efficiency in firm's course of sustainable practices by evaluating its impact on environmental performance. The results of PLS-SEM confirm that organizational reputation and green intellectual capital have positive and significantly influenced on environmental performance. The results of partial least square structural equation modelling confirm that a unit increase in green intellectual capital bring 0.449 unit increase in environmental performance of multinational firms in Indonesia. Moreover, a unit increase in organizational reputation also brings positive increase by 0.424 unit in environmental performance in Indonesia multinational firms. Keywords: Green intellectual capital, organizational reputation, environmental performance, Indonesia. JEL Classification: Q51, Q56, R11 DOI: https://doi.org/10.32479/ijeep.7752